ANALISIS DEBIT BANJIR DTA CILANGLA MENGGUNAKAN METODE HIDROGRAF SATUAN SCS - Adami, Khusnul Adami; Ramadan, Anri Noor Annisa; Asniar, Novi (JITSi : Jurnal Ilmiah Teknik Sipil, 2022)
Abstract – Population growth and increasing development are serious problems, especially in urban area as the center of the economy, government, trade, and industry. Changes in land use due to development and soil type can affect the surface runoff that occurs and water that can be stored in the soil through the infiltration process. NRCS-CN (Natural Resources Conservation Service Curve Number) is one method that is often used to convert rainfall into runoff. The purpose of this study was to determine the flood discharge at the Dam outlet point Langla every time the plan was repeated using the SCS (Soil Conservation Service). The data used in this study were rainfall data obtained from River Basin Organization (Ciwulan-Cilaki), Cilangla river discharge from SUP Cikaengan-Ciwulan, spatial map called DEMNAS from the Geospatial Information Agency, topographical map from Indonesia, and soil type maps from BBSLDP. Based on the results of the analysis and calibration results with the planned flood discharge at the Langla Dam, the peak discharge results using the SCS method on the 2th return period were obtained of 110.7 m3/s, the 5th return period is 270.7 m3/s, the 10th return period is 321.4 m3/s, the 20th return period is 363.3 m3/s, these 25th period is 397.2 m3/s, the 50th return is 518.1 m3/s, the 100th return is 668.4 m3/s, the 1000th return is 1490.9 m3/s. Keywords — Synthetic Unit Hydrograph (HSS), SCS, Discharge, Flood, Cilangla River Basin Abstrak – Pertambahan jumlah penduduk serta pembangunan yang meningkat menjadikan permasalahan yang cukup serius, terutama di wilayah perkotaan yang menjadi pusat perekonomian, pemerintahan, perdagangan serta perindustrian. Perubahan tataguna lahan akibat pembangunan serta jenis tanah dapat mempengaruhi limpasan permukaan yang terjadi dan air yang dapat disimpan ke dalam tanah melalui proses infiltrasi. NRCS-CN (Natural Resources Conservation Service Curve Number) adalah salah satu metode yang sering digunakan untuk memodifikasi hujan menjadi limpasan. Tujuan dari penelitian ini adalah untuk mengetahui debit banjir di titik outlet Bendung Langla setiap kala ulang rencana dengan menggunakan metode SCS (Soil Conservation Service), Data yang digunakan dalam penelitian ini yaitu data curah hujan dari tahun 2011 s/d 2021 yang diperoleh dari BBWS (Ciwulan-Cilaki), debit sungai Cilangla dari SUP Cikaengan-Ciwulan, DEMNAS dari Badan Informasi Geospasial, SHP RBI dari tanah air Indonesia dan Peta jenis tanah dari BBSLDP. Berdasarkan hasil analisis serta hasil kalibrasi dengan debit rencana pada Bendung langla di dapat hasil debit puncak menggunakan metode SCS pada kala ulang 2th diperoleh sebesar 110.7 m3/s, kala ulang 5th sebesar 270.7 m3/s, kala ulang 10th seebesar 321.4 m3/s, kala ulang 20th sebesar 363.3 m3/s, kala ulang 25th sebesar 397.2 m3/s, kala ulang 50th sebesar 518.1 m3/s, kala ulang 100th sebesar 668.4 m3/s, kala ulang 1000th sebesar 1490.9 m3/s. Dari hasil analisis di dapat. Kata Kunci — Hidrograf Satuan Sintetik (HSS), SCS, Debit, Banjir